Reseña a: Ieva Réklaityté (ed.), Water in the Medieval Hispanic Society. Economic, Social and Religious Implications, Helsinki: Academia Scientiarum Fennica, 2019 (284 p.). - Martín Gutiérrez, Emilio (Riparia, 2020)
Reseña libro agua